Avaliação dos mecanismos determinantes dos efeitos cardiovasculares promovidos pelo IM-7 em ratos com hipertensão induzida pelo L-NAME : abordagens in vivo e in vitro - Anjos, Raline Mendonça dos (2010)
Imidazolidinic derivates present a wide range of biological activities, such as anti-arrhythmic and anti-hypertensive. The vasorelaxant effect of six Imidazolinic compounds was evaluated in this study. Among of this, the cardiovascular effects induced by IM-7 were evaluated using in vivo and in vitro assays. HPA-01 and IM-3 produced a reduced relaxation of rat mesenteric artery rings contracted by phenylephrine (PHE) (MR = 43.15 ± 7.69%; MR = 54.08 ± 6.59%, respectively). IM-6 e IM-2 showed vasoconstictor effects in rigns with endothelium and vasorelaxant effect when endothelium was removed. Meanwhile, HPA-02 did not induce significant vasorelaxant effect. In normotensive non-anesthetized rats, the pretreatment with L-NAME or hexamethonium did not affect the hypotensive and bradicardic effects induced by IM-7. In isolated rat atrial preparations from normotensive, IM-7 (1pM-1 mM) produced negative chronotropic (MR = 65.45 ± 11.4%; pD2 = 3.94 ± 0.02) and inotropic (MR = 68.58 ± 8,0% ; pD2 = 6.74 ± 0.05) effects. which were attenuated by atropine. In hypertensive non-anesthetized rats IM-7 (1, 5, 10, 20 e 30 mg/Kg, i.v.) induced hypotensive and bradicardic effects. These effects were abolished after pre-treatment with atropine (2 mg/Kg, i.v.). In isolated hypertensive rat mesenteric artery rings IM-7 (1pM-1 mM), elicited concentration-dependent relaxation of PHE-induced contraction (pD2 = 5.64  0.09). After removal of the vascular endothelium IM-7 effects were significantly attenuated (pD2 = 3.8 ± 0.07 p < 0.001), suggesting the participation of endothelium derived relaxant factors in the IM-7 induced vasorelaxant effect. Similar results were obtained in the presence of L-NAME (100 M), ODQ (10μM), or atropine (100 nM). In endothelium denuded rings incubed with KCl 20 mM the relaxant response was not attenuated. Furthermore, in absence of extracellular calcium, IM-7 concentration-dependently depressed the vasoconstrictions derived from CaCl2. Similar results were obtained in contractions induced by 5-HT, cumulative administration of PHE or Na3VO4. These results demonstrate that IM-7 induced best pharmacological profile comparing with the other imidazolidinic derivatives. In normotensive rats, the inotropic e chronotropic effects induced by IM-7 are probably due to activation of muscarinic receptors. In hypertensive rats, the hypotensive, bradicardic and vasorelaxant effects seem to involve muscarinic receptor activation. Furthermore, IM-7 exerts a vasorelaxant effect by inhibiting calcium influx and contractile apparatus.